Rice Husk Extract and Damar Resin as Corrosion Preventing Bio Coating Materials for Mild Steel in Demineralized Water - Hidayatullah, Andra; Irawan, Anton; Pramudita, Marta (World Chemical Engineering Journal, 2023)
Corrosion is one of the main problems in industry, especially in cooling systems, refinery units, pipelines, chemicals, oil and gas production units, boilers and water processing, paints, pigments, lubricants, and others. The research focused on testing the ability of bio-coating materials of rice husk extract and resin gum using the weight loss method. In contrast, the corrosive medium used was demineralized water. The variations used were soaking time (1, 2 and 3 hours), silica concentration in bio-coating (0, 500, 1000 and 1500 ppm) and temperature (40, 60 and 80oC). From the results of this study, the highest efficiency was 87.39% at a soaking time of 1 hour and a concentration of 1500 ppm. The higher the temperature, the inhibition efficiency decreases; this shows the adsorption mechanism is physisorption.